2012
DOI: 10.4187/respcare.01653
|View full text |Cite
|
Sign up to set email alerts
|

Blow-by as Potential Therapy for Uncooperative Children: An In-Vitro Study

Abstract: At 4 cm, the Pari system delivered more drug than Respironics at 0 cm, suggesting adequate therapy during blow-by for some systems. Our results indicate that pediatric aerosol delivery is a strong function of the nebulizer system as a whole, and not simply a function of blow-by distance from the face or nebulizer efficiency. In uncooperative children, blow-by can be an effective means of drug delivery with the appropriate nebulizer system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…[35][36][37][38] One study 39 showed the opposite effect in a pediatric lung model, wherein a standard bottom-loaded aerosol mask resulted in greater drug delivery than a frontloaded design. It is important to note that a common nebulizer was not used with each of the different face masks during the testing, so it is unclear if these results were based solely on the mask or the nebulizer being used.…”
Section: Interface Selectionmentioning
confidence: 99%
“…[35][36][37][38] One study 39 showed the opposite effect in a pediatric lung model, wherein a standard bottom-loaded aerosol mask resulted in greater drug delivery than a frontloaded design. It is important to note that a common nebulizer was not used with each of the different face masks during the testing, so it is unclear if these results were based solely on the mask or the nebulizer being used.…”
Section: Interface Selectionmentioning
confidence: 99%
“…11,12,27 Lin et al 11 compared the effect of front-loaded versus angle-loaded and bottomloaded masks on inhaled mass behind the oral opening of a mannequin face when delivering the aerosol with a jet nebulizer placed 0, 1, and 2 cm from the face using an infant breathing pattern (V T of 60 mL, breathing frequency of 20 breaths/min, inspiratory time of 0.7 s). The frontloaded nebulizer was the most efficient interface and showed a 38% decrease in inhaled mass when the mask was moved 2 cm from the face.…”
Section: Interfacesmentioning
confidence: 99%
“…As stated previously, other non-anatomically correct models overestimate drug delivery to infants and children. 11,12,[26][27][28] Three other nasal interfaces were used: the VixOne PediNeb pacifier with an angled connector or with a T-piece connector and the B&B pacifier adapter. With the jet nebulizer, the nasal interfaces showed equivalent lung dose to the face mask placed 2 cm from the face when used with the infant and newborn breathing patterns, but lower lung dose with the child breathing pattern.…”
Section: Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Three commercially available nebulizer/compressor/face mask systems (Pari Sprint, Respironics Sidestream, and Salter 8900) were used to nebulize budesonide at 0, 2, and 4 cm from the face. Inhaled drug mass and the deposition on face, eyes, and mask were measured.…”
Section: See the Original Study On Page 2004mentioning
confidence: 99%